Penerapan Metode TAM Dalam Analisis E-Learning Pada SD Laboratorium UNG - Shaniyah Alhayu Paudi; Rahman Takdir; Moh Ramdhan Arif Kaluku (Diffusion: Journal of Systems and Information Technology, 2021)
AbstractE-learning is a form of information technology development utilized by an educational institution for academic enhancement purposes. Sekolah Dasar Laboratorium of State University of Gorontalo is an elementary school implementing e-learning based system concerning the use of applications such as YouTube, Microsoft team, and Google form. However, several challenges are found during its implementation. For instance, some teachers entering retirement age find e-learning difficult to be implemented. The students also find it boring during its implementation. This research employs the Technology Acceptance Model (TAM) with four basic constructs, namely Perceived Ease of Use (PEOU), Perceived Usefulness (PU), Attitude Toward Using (ATU), and Acceptance System (ACC). Findings reveal that the hypothesis testing 1 of PEOU has a significant effect on PU, the hypotesis testing 2 of PEOU has an instignificant effect on ATU, the hypotesis testing 3 of PU and ATU have an insignificant effect on teachers, but it has a significant effect on students, the hypotesis testing 4 of PU has a significant effect on ACC, the hypotesis testing 5 of ATU has an insignificant effect on ACC, the hypotesis testing 6 of PEOU and PU have a simultaneous and insignificant effect on teachers, but they have a simultaneous and significant effect on students, the hypotesis testing 7 of PEOU and ATU have a simultaneous and significant effect on ACC.Keywords: Technology Acceptance Model (TAM), e-learning, LABORATORIUM UNG.